A Boundary Value Problem for Bihypermonogenic Functions in Clifford Analysis. (17th July 2014) - Bian, Xiaoli; Qiao, Yuying
Abstract : This paper deals with a nonlinear boundary value problem for bihypermonogenic functions in Clifford analysis. The integrals of quasi-Cauchy's type and Plemelj formula for bihypermonogenic functions are firstly reviewed briefly. The nonlinear Riemmann boundary value problem for bihypermonogenic functions is discussed and the existence of solutions is obtained, which also indicates that the linear boundary value problem has a unique solution.